Autoantibody-catalyzed hydrolysis of amyloid ß peptide - Taguchi, H.; Planque, S.; Nishiyama, Y.; Symersky, J.; Boivin, S.; Szabo, P.; Friedland, R.; Ramsland, Paul; Edmundson, A.; Weksler, M.; Paul, S. (The American Society for Biochemistry and Molecular Biology Inc, 2008)
We describe IgM class human autoantibodies that hydrolyze amyloid ß peptide 1-40 (Aß40). A monoclonal IgM from a patient with Waldenström's macroglobulinemia hydrolyzed Aß40 at the Lys-28 - Gly-29 bond and Lys-16 - Ala-17 bonds. The catalytic activity was inhibited stoichiometrically by an electrophilic serine protease inhibitor. Treatment with the catalytic IgM blocked the aggregation and toxicity of Aß40 in neuronal cell cultures. IgMs purified from the sera of patients with Alzheimer disease (AD) hydrolyzed Aß40 at rates superior to IgMs from age-matched humans without dementia. IgMs from non-elderly humans expressed the least catalytic activity. The reaction rate was sufficient to afford appreciable degradation at physiological Aß and IgM concentrations found in peripheral circulation. Increased Aß concentrations in the AD brain are thought to induce neurodegenerative effects. Peripheral administration of Aß binding antibodies has been suggested as a potential treatment of AD. Our results suggest that catalytic IgM autoantibodies can help clear Aß, and they open the possibility of using catalytic Abs for AD immunotherapy. © 2008 by The American Society for Biochemistry and Molecular Biology, Inc.